Roman de la route et imaginaire du “Far East” québécois:: fleuve, fémininité et origines chez Francine Lemay et Noël Audet - Laporte, David (Ponti/Ponts, 2021)
This article explores the hypothesis of the pervasiveness of the “Far East” imaginary in Quebec’s literature. The core of this eastern imaginary is usually structured around representations of the St-Lawrence River, a presence symbolically feminized in which its symbolism contaminates the whole landscape it borders. In the road novel Ah, l’amour l’amour (1981) of Noel Audet and Évagabonde (1981) from Francine Lemay, we have the privilege of experiencing more precisely those landscapes associated to its femininity, to its maternity and its origin, three values, among others, of which the imaginary of Quebec’s Far East is built upon.